1 ANALISIS PENGARUH KUALITAS PELAYANAN, PROMOSI DAN LOKASI TERHADAP MINAT BERKUNJUNG PADA KEBUN BINATANG MEDAN - kristina oktaviyani (Jurnal Media Informasi Manajemen, 2013)
This study aims to determine the effect of service quality, promotion and location of the intention to visiting the Medan Zoo, and which variables most affect intention to visiting the Medan Zoo.The study population is a Medan Zoo visitors. The research sample was taken by 99 people. The analysis method used is descriptive analysis method and the method of multiple linear regression analysis. The data used in this study is primary data and secondary data. Primary data was collected through questionnaires techniques, the measurement using Likert scale.The results obtained in this study indicate that the quality of service, promotion and location simultaneously have a positive and significant impact on interest in visiting the Medan Zoo, while the partial promotion variables have a dominant influence on interest in visiting the Medan Zoo.Kata Kunci: Kualitas Pelayanan, Promosi, Lokasi dan Minat Berkunjung.Keywords : Quality of Service, Promotion, Location and Intention to visit.